Current Advances in CETSA - Tolvanen, Tuomas Aleksi (Frontiers in Molecular Biosciences, 2022)
Knowing that the drug candidate binds to its intended target is vital part of drug discovery. Thus, several labeled and label free methods have been developed to study target engagement. In recent years, the Cellular Thermal Shift Assay (CETSA) with its variations has been widely adapted to drug discovery workflows. Western blot based CETSA is used primarily to validate the target binding of a molecule to its target protein whereas CETSA based on bead chemistry detection methods (CETSA HT) has been used to screen molecular libraries to find novel molecules binding a pre-determined target. Mass spectrometry based CETSA is also known as thermal proteome profiling (TPP) has emerged as a powerful tool for target deconvolution and finding novel binding partners for old and novel molecules. With this technology it is possible to probe thermal shifts among over 7000 proteins from one sample and to identify the wanted target binding but also binding to unwanted off-targets known to cause adverse effects. In addition, this proteome wide method can provide information of the biological process initiated by the ligand biding. The continued development of mass spectrometry labelling reagents, such as isobaric tandem mass tag technology (TMT) continues to increase the throughput of CETSA MS allowing its use for structure activity relationship (SAR) studies with a limited number of molecules. In this review we discuss the differences between different label free methods to study target engagement but with our focus is on CETSA and recent advances in CETSA method.